Produção familiar do camarão Litopenaeus vannamei (Boone, 1931): viabilidade e qualidade - Rolim, Nathiene Patrícia Ferreira de Amaral (2015)
The traditional shrimp farming has been associated with many negative environmental impacts on mangrove ecosystems, apicuns and areas of slopes, including the release of effluent, usually with high organic matter content, from the offered feed and droppings of shrimps. In this sense, it is essential that the food offered are appropriate with effective and environmentally sustainable costs, as the inappropriate use of feed can compromise both animal development and the environment. In order to meet the demand for seafood products, with quality and adequate nutritional value, employment of shrimp farming techniques in tanks associated with the production of organic food can be a viable alternative to obtain a product of good quality, environmentally responsible and with added commercial value. The purpose of this study was to evaluate the organic cultivation of shrimp Litopenaeus vannamei (Boone, 1931) along the lines of family production, fed organic feed, produced from food waste and industrial feed. In tanks with organic feed, animals still were attended to perifítons as additional power. In order to evaluate the two types of crops, were determined some physicochemical and microbiological parameters of the water and shrimps, the bromatologia the feed, the farmed shrimp, plus the biometrics of animals. The results were compared with each other and with existing environmental and health laws, to evaluate the proposed treatment and quality of farmed animals. The data indicated that there was no significant difference between the crops, as regards the nutritional and microbial composition of the animal, as well as the quality of the water tanks. Therefore, one can understand that organic food associated with regular supply of perifítons, is an acceptable alternative to replacement of industrial feed the family shrimp farming due to low cost of production, absence of additives and preservatives, waste recovery generated by community and the possibility of improving the quality of life of fishermen whose activity is increasingly threatened by commercial fishing development.